Thermal Stability Improvement of Alkaline Protease AprEbl by Rational Design and Its Potential Mechanism - LUO Yanni, HU Liuxiu, LIU Zhiyu, GAO Xuli, CHEN Yu, WU Chuanchao, LIU Yan (Shipin Kexue)
To obtain alkaline protease with enhanced thermal stability and catalytic activity, this study focused on the alkaline protease AprEbl derived from Bacillus licheniformis B66. Using molecular dynamic simulations, residues N183, G186, S265, S267, and Y320 in AprEbl were identified as highly flexible regions. Computer-aided design was employed to propose mutation sites, and five single-point mutant enzymes were generated using site-directed mutagenesis. Their enzymatic properties were subsequently investigated. Two advantageous mutants were selected for a second round of combinatorial mutagenesis. The results demonstrated that the double mutant S265H/S267F exhibited significantly improved thermal stability compared with the wild-type enzyme, although their specific activities were on par with each other. The half-life of this mutant increased by 7.35-fold at 55 ℃ and 5.01-fold at 75 ℃. Other single-point mutants also displayed better high-temperature tolerance than the original enzyme. This study provides a theoretical foundation for improving the enzymatic properties of alkaline proteases via protein engineering to meet industrial demands.